Lycopene in feed as antioxidant and immuno-modulator improves broiler chickens performance under heat-stress conditions - Hidayat, Dalila Fadhila; Mahendra, Mohamad Yusril Nur; Kamaludeen, Juriah; Pertiwi, Herinda (Wiley, 2023)
Lycopene is a type of carotenoid pigment widely distributed in various plants and fruits, with tomatoes, carrots, and guava being the most abundant sources. Due to its high content of beneficial active components, lycopene has been used in medicine, where it is employed as a dietary additive for cancer therapy, immune modulator, and feed additive to improve livestock productivity. Lycopene is a lipophilic substance that can act as either a prooxidant or a free radical scavenger and is particularly efficient in enhancing broiler performance. Furthermore, lycopene can alleviate heat stress by improving the activity of various antioxidant enzymes such as superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), as well as increasing the total antioxidant capacity (T-AOC) and nuclear muscle factor erythroid 2-related factor 2 (Nrf2), while simultaneously reducing the levels of malondialdehyde (MDA) and muscle Keap1 expression. In addition, lycopene can improve broiler fertility by enhancing sperm performance and reducing inflammation by modulating the levels of interleukin 1, 2, and 10 (IL-1, IL-2, and IL-10) in cases of infection. In cases of disease by aflatoxin B1 (AFB1), lycopene can modulate interferon-γ (IFN-γ), IL-1, claudin-1 (CLDN-1), and zonula occludens-1 (ZO-1). Furthermore, under the lipopolysaccharide challenge, lycopene can increase the relative weights of immune organ indices such as the bursal, spleen, and thymus.